Analisis Pengaruh Perubahan Nilai Total Moisture, Ash Content dan Total Sulphur Terhadap Nilai Kalori Batubara Bb-50 Di Tambang Banko Barat Pt. Bukit Asam, Tbk. Tanjung Enim Sumatera Selatan - Muhammad Agil Fadhili; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. One type of coal mined at PT Bukit Asam, Tbk is BB-50, in the distribution of coal there are found differences in the quality of coal. This study aims to obtain differences in calorific value (GCV), total moisture, ash content and total sulfur on front, stockpile and railway carriage and the effect of these parameters on calorific value (GCV). The analysis uses statistical methods that’s descriptive statistics, independent samples t-test, one way ANOVA, correlation  and regression. Average calorific value (GCV) on fronts, stockpile and railway carriage respectively are 5037 Kcal/KgAr, 4928 Kcal/KgAr and 4869 Kcal/KgAr, the average of total moisture value respectively are 27.87%Ar, 27.84%Ar and 29.49%Ar, the average of ash content value respectively are 2.01%Ar, 4.01%Ar and 3.63%Ar and the average of sulfur value respectively are 0.49%Ar, 0.41%Ar and 0.51%Ar. Parameters that experience significant differences from front to the railway carriage are the calorific value has decreased by 96,056 - 240,610 Kcal/KgAr, total moisture has increased by 0,851 - 2,38%Ar and ash content has increased by 1,6 - 2,18%Ar. The effect of total moisture, ash content and total sulfur on calorific value is expressed in the equation GCV = 641,204 + 1,029TS - 63,781TM - 57,69ASH.Keywords: Coal Quality, Statistical Analysis, Front, Stockpile, Railway Carriage